Analysis of Stock Market Development, Foreign Private Investment and Economic Growth in Nigeria. (June 2018) - Anthony-Orji, Onyinye I.; Orji, Anthony; Ogbuabor, Jonathan E.
The study estimated the impact of stock market development and foreign private investment on economic growth in Nigeria over the period of 1985–2016, using secondary data from various publications of the Central Bank of Nigeria. The ordinary least square (OLS) technique was employed in this study, while the Engel and Granger co-integration approach was applied to determine the long-run relationship between the variables. The result showed that market capitalisation, all share index and real exchange rate have statistically significant impact on economic growth, while foreign direct investment, trade openness and gross national savings have insignificant impact on growth. The study also showed that there is a long-run relationship among stock market development, foreign private investment and economic growth in Nigeria. The error correction model (ECM) results showed that the model adjusts to equilibrium in the short run and that about 51 per cent of the disequilibrium between gross domestic product and the independent variables is corrected each year. The study recommended that policymakers and monetary authorities should gear efforts towards formulating policies that will fine-tune stock market performance and reduce issues, such as, unpaid dividends, delay in dividend payments and unhealthy transfer of stocks. This is pertinent to encourage greater population of the citizenry to invest in the stock market. Finally, the study concluded that provision and improvement of infrastructure and power as well as enforcement of investor-friendly policies by the government is needed as these will encourage the establishment of more firms and industries that will participate in the stock market, thereby contributing to the growth of the economy. JEL Classification: E22, F21, F43, O16